Analysis of physical properties in three mango varieties processed with indirect solar and electric drying - Díaz Guerrero, Teresa de Jesús; Castillo Telléz, Margarita; Torres García, Alberto Francisco (Acta Universitaria, 2026)
Mexico is one of the leading exporters of mangoes but faces post-harvest losses of up to 40%. This study evaluated the effect of indirect tunnel solar drying and non-convective electric oven drying on the physical and colorimetric properties of Manila, Ataulfo, and Oro mangoes. Moisture content, weight loss, water activity, and CIE-Lab parameters (L*, a*, b*) were analyzed. Both methods reduced moisture content to below 8%, inhibiting microbial growth. However, differences in color were observed: all samples showed a decrease in yellowness (b*) and an increase in redness (a*), which were more intense in the electric oven. Indirect solar drying better preserves brightness and yellow-orange tones. The Oro variety showed the greatest color variation (∆E > 40), possibly due to its rich composition of sugars and polyphenols. These results support solar drying as a sustainable alternative for mango preservation.